Field Evaluation of Different Pre-Wetting Ratios for Sustainable Salting. Issue 6 (June 2019) - Usman, Taimur; Fu, Liping; Kaur, Jaspreet
This research presents the findings from a field study aimed at comparing the performance of different pre-wet (PW) ratios of salt for their impacts on snow melting performance/friction of road surfaces. The research was motivated by the question of whether or not better snow melting performance can be achieved by using higher PW ratios. Field tests were conducted on three sections of a provincial highway, located in Western Ontario in the winter season of 2016/2017 under three PW ratios, 5% (current practice), 10%, and 20%. Promelt Mag 22 (22% magnesium chloride, MgCl2, concentration) was used for pre-wetting. Based on a comprehensive statistical analysis of the field testing data, it was found that salt pre-wetted at 20% improved friction levels by approximately 12% while reducing the salt usage by 19% and sand by 35% when compared with usages at a PW ratio of 5%. Examination of images collected during snow storms showed that sections treated with salts with higher PW ratios generally had lower snow coverage.